2011
DOI: 10.1111/j.1365-2591.2011.01985.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and smear layer removal ability of a novel irrigant, QMiX

Abstract: QMiX and NaOCl were superior to CHX and MTAD under laboratory conditions in killing E. faecalis and plaque bacteria in planktonic and biofilm culture. Ability to remove smear layer by QMiX was comparable to EDTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
233
2
23

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(270 citation statements)
references
References 44 publications
12
233
2
23
Order By: Relevance
“…18,19,28,35 QMiX was able to open dentinal tubules without causing erosion (Figure 2A). These findings are in agreement with those of previous studies and with the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19,28,35 QMiX was able to open dentinal tubules without causing erosion (Figure 2A). These findings are in agreement with those of previous studies and with the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 QMiX is recommended after the use of sodium hypochlorite (NaOCl) during root canal instrumentation 18,19 and is effective in removing the smear layer. [18][19][20] Therefore, the present study aimed to evaluate the effects of QMiX, 17% EDTA, 10% citric acid (CA), 1% peracetic acid (PA), 2.5% NaOCl (solution control), and distilled water (negative control) on microhardness reduction and erosion of human root canal dentin. The null hypothesis is that no irrigation protocol reduces microhardness or causes erosion in human root canal dentin.…”
Section: Introductionmentioning
confidence: 99%
“…This is a premixed and ready to use irrigating solution that contains EDTA, chlorhexidine (CHX) and a detergent (cetrimide), with pH slightly above neutral. This irrigant has demonstrated antibacterial activity comparable to NaOCl and superior activity against planktonic and biofilm bacteria compared to 2% CHX and MTAD (13). Contrarily, Ordinola-Zapata et al (21) observed the poor antibacterial activity when QMiX was applied for 5 min on multispecies biofilm from oral microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The most important requirements for an ideal endodontic irrigant are to have an antibacterial effect and to penetrate deep into the dentinal tubules. In the last few years, new irrigant solutions for smear layer removal with added antimicrobial agents have been developed (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new irrigation solution containing ethylenediaminetetraacetic acid (EDTA), chlorhexidine, and a nonspecified detergent has been introduced called QMix 2in1 (Dentsply Tulsa Dental, Tulsa, OK) 7 . Studies have demonstrated that the QMix solution is an antibacterial agent and is able to remove the smear layer 7,8 .…”
Section: Introductionmentioning
confidence: 99%